Intensity-sensitive and position-resolving cavity for heavy-ion storage rings - Chen, Xin; Sanjari, Mohammad Shahab; Hülsmann, Peter; Litvinov, Yuri A.; Nolden, Fritz; Piotrowski, Jeremi; Steck, M.; Stöhlker, Thomas; Walker, P. M. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2016)
A heavy-ion storage ring can be adapted for use as an isochronous mass spectrometer if the ion velocity matches the transition energy of the ring. Due to the variety of stored ion species, the isochronous condition cannot be fulfilled for all the ions. In order to eliminate the measurement uncertainty stemming from the velocity spread, an intensity-sensitive and position-resolving cavity is proposed. In this paper we first briefly discuss the correction method for the anisochronism effect in the measurement with the cavity. Then we introduce a novel design, which is operated in the monopole mode and offset from the central beam orbit to one side. The geometrical parameters were optimized by analytic and numerical means in accordance with the beam dynamics of the future collector ring at FAIR. Afterwards, the electromagnetic properties of scaled prototypes were measured on a test bench. The results were in good agreement with the predictions.
Gesehen am 30.04.2020